Light-Driven Palladium-Radical Hybrid Species: Mechanistic Aspects and Recent Examples - Jardim, Guilherme A. M.; Dantas, Juliana A.; Barboza, Amanda A.; Paixão, Márcio W.; Ferreira, Marco A. B. (Synthesis, 2022)
Visible-light-induced palladium-mediated reactions have become a novel and promising field in organic synthesis. This photocatalytic arsenal presents complementary features towards traditional Pd chemistry, allowing the achievement of new and unique reactivities by the generation of versatile Pd-radical hybrid species. These putative intermediates can be produced by direct excitation of Pd complexes, together with organic radical precursors. This review aims at describing recent advances regarding the combination of Pd-based photocatalytic manifolds and radical generation in the functionalization of important motifs in synthetic chemistry, encompassing detailed mechanistic descriptions and relevant examples.1 Introduction2 Homolytic Cleavage of C–X Bonds3 Cyclizations, Desaturations and Atom Transfer Reactions4 Homolytic Cleavage of N–O Bonds5 Generation through Diazo Compounds6 Generation of Acyl Radicals7 Generation of Ketyl Radicals8 Conclusions
Keywords: palladium; light-driven process; photocatalysis; hybrid radical species; light-induced transition-metal catalysis